The fabrication of In2O3/In2S3/Ag nanocubes for efficient photoelectrochemical water splitting. Issue 4 (4th January 2016) - Xu, Rui; Li, Haohua; Zhang, Wenwen; Yang, Zepeng; Liu, Guiwu; Xu, Ziwei; Shao, Haicheng; Qiao, Guanjun
Abstract : Three-component In2 O3 /In2 S3 /Ag heterostructured nanocubes synthesized by electrodeposition show a significantly enhanced photoelectrochemical water splitting performance. Abstract : In this work, for the first time, a three-component In2 O3 /In2 S3 /Ag nanocomposite heterostructured photoanode is prepared on a F-doped SnO2 (FTO) glass substrate. The three-component photoanode exhibits significantly enhanced photoelectrochemical properties compared with the single-component (In2 O3 ) and two-component (In2 O3 /In2 S3 or In2 O3 /Ag) systems. Ag nanoparticles deposited on the surface of In2 O3 /In2 S3 nanocubes can facilitate the separation of photogenerated charge carriers and enhance the absorption of visible light. In I – V curves, the In2 O3 /In2 S3 /Ag photoanode generates a remarkable photocurrent density of 8.75 mA cm −2 (at 0 V vs. SCE), which is higher than those of the two-component In2 O3 /In2 S3 (4.47 mA cm −2 ) and In2 O3 /Ag (3.50 mA cm −2 ). Furthermore, it also gives efficiency as high as 67% around 350 nm in the incident photon to electron conversion efficiency (IPCE) spectrum. These results open up a promising avenue for the design and fabrication of novel heterojunctions for photoelectrochemical water splitting.